ANALISIS MAKNA PADA PUISI “AKU INGIN” KARYA SAPARDI DJOKO DAMONO MENGGUNAKAN PENDEKATAN SEMIOTIKA - Rian Moh Sobirin; Teti Sobari; Woro Wuryani (IKIP Siliwangi, 2021)
Sapardi Djoko Damono’s poem entitled Aku Ingin have a simple verse, but has a very deep meaning. This poem was written for his beloved wife, because at that time Sapardi’s wife was ill. Sapardi Djoko Damono is a writer and professor at the Faculty of Letters, University of Indonesia, he was able to write the poem Aku Ingin in just 15 minutes. Because this poem has a very deep meaning, the writer used it as research material. The purpose of this research is to analyze the meaning in Sapardi Djoko Domono’s poem entitled Aku Ingin in semiotics, to describe the results of the analysis of the poem entitled Aku Ingin, and to define the main problems in the theme of the poem. The method used is descripted method, wchis is to tell the contebts of the analyzed is dissected using a semiotic approach. The results show that this poem is an expression the the love he experinces does not reach his idol’s heart. The results of analyzing this poem are the symbols in the first, second, and fifth verses. Icons are on repeated verses. And the index is inthe third and sixth stanzas which use personafication figures.